2020
DOI: 10.13106/jafeb.2020.vol7.n10.729
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Indian Private Sector Bank Efficiency: Non-Stochastic Frontier DEA Window Analysis Approach

Abstract: The study examines the efficiency of private sector banks in India with the help of Window DEA (Data Envelopment Analysis) for a period from 2005 to 2017. With a window of three years, the period was divided into 11 windows. The study outcomes show that 59.9% of all private sector banks in India operate at more than 0.9 level of efficiency, and there are only three occasions when banks were operating at the efficiency value between 0.6 to 0.7. Further, the consistency in the efficiency scores of the banks has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Conversely, the perceived interest rate risks led to holding back loan growth for banks' sensitivity to interest rate changes (Nguyen & Dang, 2020). Kumar et al (2020) tested the efficiency of the Indian private banking sector using the DEA approach from 2005-2017. The results showed that 59.9% of banks operate at more than 0.9 level of proficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, the perceived interest rate risks led to holding back loan growth for banks' sensitivity to interest rate changes (Nguyen & Dang, 2020). Kumar et al (2020) tested the efficiency of the Indian private banking sector using the DEA approach from 2005-2017. The results showed that 59.9% of banks operate at more than 0.9 level of proficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This potential for expansion has amplified competition, and banks are facing hurdles in keeping productive in order to compete. Consequently, academicians, administrators, and regulators have all expressed a strong interest in banking sector productive efficiency studies (Andries, 2011;Sharma et al, 2013;Giolongo and Gomila, 2016;Kumar et al, 2020) and a critical part of management in practice (Wanke et al, 2015). Every decision-making unit (DMU) benefits from implementing productive performance analysis (Hatami-Marbini and Toloo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, academicians, administrators, and regulators have all expressed a strong interest in banking sector productive efficiency studies (Andries, 2011; Sharma et al. , 2013; Giolongo and Gomila, 2016; Kumar et al. , 2020) and a critical part of management in practice (Wanke et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, very few studies have focused on the bi-directional relationship between risk-taking, capital regulation, and efficiency (Altunbas et al, 2007;Deelchand & Padgett, 2009;Fiordelisi et al, 2011;Tan & Floros, 2013). Besides, there is an increasing number of research interests on capital regulation (Nguyen & Dang, 2020;Zheng et al, 2017), risk-taking (Hossain, Moudud-Ul-Huq, & Kader, 2020;Tran, Do, & Nguyen, 2020), and efficiency (Kumar, Anand, & Batra, 2020;Moudud-Ul-Huq et al, 2020).…”
Section: Introductionmentioning
confidence: 99%